Analysis on factors influencing students financial literacy - Ade Gunawan; Murviana Koto (Proceedings of AICS - Social Sciences, 2017)
Financial literacy has become a hot issue to be discussed nowadays. This is because the mastery on finance can lead to financial welfare. Education highly contributes in the increment of financial literacy, and this research focuses on how gender, age, parents’ income and University affect in students’ financial literacy. This research is done to 451 Economic and Business students by using accidental sampling. Financial literacy is analyzed with descriptive analysis and factor analysis with Confirmatory Factor Analysis (CFA) using Structural Equation Model (SEM). The result shows that age, gender, and parents’ income affect students’ financial literacy in significant way, while University lincome doesn’t affect in significant way.